Total hydrogenation of bio-derived furans over supported Ru subnanoclusters prepared via amino acid-assisted deposition. Issue 3 (10th January 2020) - Qian, Yang; Li, Ze-Jun; Du, Xian-Long; Zhang, Qi; Zhao, Yi; Liu, Yong-Mei; Cao, Yong
Abstract : Development of efficient catalyst with reduced noble metal usage is extremely desirable for selective hydrogenations of furan-containing bio-based feedstocks, which represents an attractive and sustainable alternative to petrochemical resources. Abstract : Development of a highly efficient and robust catalyst with reduced usage of noble metals is extremely desirable for selective hydrogenations of furan-containing bio-based feedstocks, which represents an attractive and sustainable alternative to petrochemical resources. Herein, we describe a new type of well-dispersed Ru subnanoclusters ( ca. 0.50 wt%) supported on commercial P25 TiO2 material obtained from a facile and effective amino acid-assisted deposition–precipitation strategy. The as-synthesized catalyst exhibits superior catalytic activity and selectivity for direct hydrogenation of industrially important furfural as well as a range of structurally diverse bio-based furanic compounds to their corresponding fully hydrogenated derivatives. An average turnover frequency (ATOF) value as high as 367 h −1 at 80 °C and 4 MPa H2 is obtained, which is the highest reported value. This catalyst also shows stable furfural total hydrogenation in 5 reaction cycles conducted at 80 °C (52 mmol-scale, turnover number up to 12 500). In terms of the kinetic and structural characterizations, the key performances of the ultrasmall Ru clusters are proposed to mainly originate from an enhanced number of unsaturated surface Ru atoms and change in local coordination environment. Our work highlights the importance of the subnanometric size of Ru clusters in the advancement of efficient and affordable approaches towards bio-based chemical production.